DSP-0509, a TLR7 agonist, exerted synergistic anti-tumor immunity combined with various immune therapies through modulating diverse immune cells in cancer microenvironment - Ota, Yosuke; Inagaki, Ryosaku; Sumida, Kentaro; Nakamura, Megumi; Nagai, Yasuhiro; Yamamoto, Setsuko (Frontiers in Oncology, 2024)
Toll-like receptor 7 (TLR7) acts as a crucial component of the innate immune system. Upon TLR7 binding to its ligand, myeloid cells, including dendritic cells (DCs) and macrophages, are activated and play vital roles in initiating adaptive immunity. Consequently, TLR7 agonists have been employed in cancer immunotherapy. We have synthesized DSP-0509, a systemic injectable TLR7 agonist, and in this investigation, we examined the effects of DSP-0509 on tumor-infiltrating lymphocytes (TILs) utilizing single-cell RNA sequencing (scRNA-seq) in a mouse model bearing tumors. Our results demonstrated that DSP-0509 induced an expansion of immune cell populations, such as Natural Killer (NK) cells, CD4+ T cells, and CD4+ regulatory T cells (Tregs). Subsequently, we combined an Indoleamine 2,3-dioxygenase 1 (IDO1) inhibitor with DSP-0509 to enhance the antitumor efficacy by reducing Tregs, as DSP-0509 led to an increase in Treg presence within tumors. Our findings demonstrated that this combination therapy effectively reduced Treg infiltration within the tumor, leading to enhanced antitumor activity. To further prevent CD8+ T cell exhaustion, we combined DSP-0509 with an anti-PD-1 antibody and assessed the alterations in TILs using scRNA-seq. Our results indicated that the combination treatment significantly increased the cluster of CD8+ T cells expressing Gzmb, Prf1, Ctla4, and Icos, when compared to the administration of DSP-0509 alone. Additionally, we observed a marked rise in the M1-like macrophage cluster in the combination treatment group compared to the group receiving only DSP-0509. To validate the potential of modulating myeloid cells within the tumor to enhance antitumor efficacy, we combined DSP-0509 with an inhibitor targeting the receptor tyrosine kinase AXL. In bone marrow derived macrophages (BMDMs), the AXL inhibitor further amplified DSP-0509-stimulated TNFα secretion while reducing IL-10 secretion. As a final step, we evaluated the antitumor activity by combining DSP-0509 and the AXL inhibitor in an in vivo tumor model, which demonstrated increased efficacy. In summary, our study elucidated the effects of DSP-0509 on immune activity within the tumor microenvironment. These findings provided valuable insights that pave the way for the development of novel combination immunotherapy strategies.